'Slow to change': Farmers' perceptions of place-based barriers to sustainable agriculture. Issue 6 (12th January 2017) - Grover, Samantha; Gruver, Joshua
Abstract: Smallholder farmers are an important and growing segment of the farm population in Indiana and in the USA. Past research regarding farmer decision-making has been inconsistent and has largely focused on the larger-scale, conventional farmer, leaving smallholders poorly understood. There is a need to better understand the management decisions of smallholder farmers within their regional context to promote efforts toward environmental, social and economic sustainability. Through in-depth qualitative inquiry, this study investigated the impact of regional factors that influence farmers' decisions and the barriers and opportunities most relevant to farm viability and sustainability in the context of East Central Indiana (ECI). Semi-structured interviews with 15 key informants and 33 farmers informed our understanding of the factors most relevant to small-scale farming in the region. Several important themes emerged related to perceived barriers to sustainable farm management, including markets; structures and regulations; time and labor; environmental/ecological factors; and networking and access to educational support. The results of this study complement the findings of previous work that describe the complex framework farmers navigate when making decisions on the farm. Further, subtle regional factors emerged that significantly impact farmers' decisions, emphasizing the importance of local context in crafting agricultural policies and outreach efforts. Implications and recommendations for ECI are discussed.